2011
DOI: 10.1016/j.jneumeth.2011.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Organotypic vibrosections: Novel whole sagittal brain cultures

Abstract: Highlights► Novel whole brain sagittal organotypic vibrosection in vitro model. ► Survival of cholinergic and dopaminergic neurons. ► Capillaries in whole brain sections in vitro. ► Long nerve fiber growth with neurotracing (Mini-Ruby). ► Striato-nigral varicosities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…In the present work, brain sagittal slices were used since they contain in a unique slice many anatomical structures as corpus callosum, cortex, hippocampus, striatum, globus pallidus, SN and cerebellum among others. In addition, many of the original neuronal connections between brain structures are better preserved in brain sagittal slices (Ullrich et al, 2011). Furthermore, the subgranular zone of the dentate gyrus and the subventricular zone, two neural stem cell niches, are conserved which allows to study neurogenesis (Garzon-Muvdi and Quinones-Hinojosa, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, brain sagittal slices were used since they contain in a unique slice many anatomical structures as corpus callosum, cortex, hippocampus, striatum, globus pallidus, SN and cerebellum among others. In addition, many of the original neuronal connections between brain structures are better preserved in brain sagittal slices (Ullrich et al, 2011). Furthermore, the subgranular zone of the dentate gyrus and the subventricular zone, two neural stem cell niches, are conserved which allows to study neurogenesis (Garzon-Muvdi and Quinones-Hinojosa, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the subgranular zone of the dentate gyrus and the subventricular zone, two neural stem cell niches, are conserved which allows to study neurogenesis (Garzon-Muvdi and Quinones-Hinojosa, 2009). Sagittal sections remain the most complete type of organotypic slices since they allow the observation of cholinergic, GABAergic and dopaminergic neurons as well as of vascular brain capillaries or cortico-striatal and cortico-hippocampal nerve fibers (Kearns et al, 2006; Ullrich et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperphosphorylated form of tau is known to form intraneuronal neurofibrillary tangles (NFTs) (22). An increasingly accepted hypothesis of toxicity argues that tau oligomers which appear in the initial phases of tangle formation are the most toxic species (23)(24)(25)(26)(27)(28)(29)(30)(31). Recently published works support the idea that prefibrillar soluble oligomers of amyloidogenic proteins, including α-synuclein and amyloid-beta (Aβ) are more toxic than insoluble LBs and senile plaques (32)(33)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Humpel group used sagittal brain slices, and for the first time showed that dopamine neurons survive despite the non-functional striatonigral pathway. [117] Organotypic hippocampal slice cultures represent a good model for studying AD pathology, given that the hippocampal is a strategic region in AD patients that exhibits early neurodegeneration. [114,118] Several groups also used this model as widely accepted platform to study A β toxicity.…”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%